2020
DOI: 10.1128/mbio.00436-20
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic and Viral Community Composition of Freshwater Springs in Florida, USA

Abstract: Aquifers, which are essential underground freshwater reservoirs worldwide, are understudied ecosystems that harbor diverse forms of microbial life. This study investigated the abundance and composition of prokaryotic and viral communities in the outflow of five springs across northern Florida, USA, as a proxy of microbial communities found in one of the most productive aquifers in the world, the Floridan aquifer. The average abundances of virus-like particles and prokaryotic cells were slightly lower than thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 76 publications
1
21
0
Order By: Relevance
“…On 6/12/17, 7/17/17, 8/8/17, 8/21/17, 9/11/17, 9/25/17, 10/30/17, and 5/7/18 the iron chloride procedure was used on the pond water after sequential 1 μm and 0.2 μm filtration, with the 0.2 μm a common pore size used in virome generation to prevent cellular contamination [ 33 , 37 , 42 ]. A 1 mL solution of FeCl 3 (4.83 g FeCl 3 into 100 ml H 2 O) was added to the filtered pond water and incubated in the dark for 1 h. The samples were then filtered onto 142-mm 1 μm polycarbonate filters (Sigma-Aldrich, MO, United States) to capture flocculated viral particles [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On 6/12/17, 7/17/17, 8/8/17, 8/21/17, 9/11/17, 9/25/17, 10/30/17, and 5/7/18 the iron chloride procedure was used on the pond water after sequential 1 μm and 0.2 μm filtration, with the 0.2 μm a common pore size used in virome generation to prevent cellular contamination [ 33 , 37 , 42 ]. A 1 mL solution of FeCl 3 (4.83 g FeCl 3 into 100 ml H 2 O) was added to the filtered pond water and incubated in the dark for 1 h. The samples were then filtered onto 142-mm 1 μm polycarbonate filters (Sigma-Aldrich, MO, United States) to capture flocculated viral particles [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Using metagenomics previous studies have identified that within the viral community of surface freshwater sites bacteriophages (phage) dominate [33][34][35][36][37]. Phages are critical components in shaping the evolution, diversity, abundance, and genetic composition of bacteria [38].…”
Section: Introductionmentioning
confidence: 99%
“…For the amplified DNA dataset, Cenote-Taker2 detected more total calls (5.2X all other tools combined) and more unique calls (23.8X all other tools combined), all of which have at least one type of hallmark gene. Single-stranded DNA viruses are highly abundant members of many microbial communities 12,37,38 making Cenote-Taker2’s discovery module a particular advance for researchers interested in these viruses.…”
Section: Resultsmentioning
confidence: 99%
“…Prokaryotic microbes have important roles in global biochemistry cycles, affect water quality (Mermillod-Blondin et al, 2015;Malki et al, 2020) and the dynamics of karst processes (Lian et al, 2011). However, archaea, a significant portion of the prokaryotic community in the karst environment, have not been well studied, especially for spatial and temporal variation.…”
Section: Introductionmentioning
confidence: 99%